(untitled) (Bangladesh Journal of Medical Science, 2025)
Background There is insufficient evidence regarding visual perception during pregnancy. Visual perception can be reflected by the C1 event-related potential (ERP) component. This study investigated visual perception in pregnant women by analyzing the C1 ERP component using visual oddball stimuli. Method Thirty-six participants were recruited and divided into a control group (n = 18) and a pregnant group (n = 18; 13-40 weeks of pregnancy). An ERP study used a 128-sensor net with a visual oddball task. In the oddball task, participants were asked to push either button ‘1’ if they saw ‘O’ or button ‘2’ if they saw ‘X’, as quickly and accurately as possible. The mean value of differences in standard and target stimuli was measured. Amplitudes and latencies of the C1 ERP component were analyzed in the parieto-occipital (P3, P4, O1, O2) and midline (Fz, Cz, Pz) areas using seven different electrodes. Results No significant differences in the amplitudes and latencies of the C1 ERP component were observed in the pregnant group compared to the controls. Conclusion The visual oddball-stimulated visual perception was intact in pregnant women, indicating that pregnancyrelated hormones do not negatively impact visual perception during pregnancy. BJMS, Vol. 24 No. 04 October’25 Page : 1167-1171